STANDARDIZED AGE-SPECIFIC CATCH RATES IN NUMBER OF FISH FOR THE NORTH ATLANTIC SWORDFISH (Xiphias gladius) INFERRED FROM DATA OF THE SPANISH LONGLINE FLEET DURING THE PERIOD 1982-2019 - Mejuto-García, Jaime; García-Cortés, Blanca; Ramos-Cartelle, Ana; Fernández-Costa, José (2021)
Standardized ages specific 1-5+ catch rates in number of fish were updated for a period of 38 years using log-normal General Linear Model (GLM) from 11,842 trips (145,294 fishing days, 262.8 x106 hooks) of the Spanish surface longline targeting swordfish in the North Atlantic stock. The models took into consideration factors such as gear-style and a target variable to allow for the two most important changes in fishing strategy in recent periods. The base case models explained between 41%-46% of CPUE variability. The standardized CPUE for age 1 suggests a very positive phase of recruitments between periods 1997-2012 and also 1997-2019 with an overall mean of around double the relative abundance compared to the 1982-1996 mean level. This positive phase had positive effects on other ages including ages 5+ and the subsequent demographic changes since mid-1990s onwards which could be the main cause for explaining different availabilities by size and age and different average weights and overall CPUEs between different regions-fleets. SWOATL2021 Pez espada del Atlántico (2020-2021)